Sistem Pelacak Aset Berbasis IoT - Daniel Sutopo Pamungkas; Muhammad Syafei Gozali; Abdurrahman Dwijotomo; Aliza, Siti Zurina; Herlina Sanjaya Nainggolan; A.Rizki Saputra (Politeknik Negeri Bengkalis, 2023)
The inventory system is an activity carried out by management that aims to identify, manage and know the location of the existence of goods in the building area. To reduce errors in entering asset data, a technology is needed, namely RFID (Radio Frequency Identification). The use of active RFID technology for asset tracking is by attaching tags to assets or items given a unique ID for identification and providing information on the availability of assets passing through a room. Where the type of RFID used in this system is the UHF RFID Reader type which has an ultra high frequency with Single Tag and Multi Tag testing methods. Where in testing the optimal RFID reader reading distance in the front direction with a distance of 6,5 meters. Then the RFID data is stored in the NodeMCU ESP8266 microcontroller which will then be sent to the MySQL database using the internet, then synchronized with the interface, so that the system is able to register each asset, then display the asset data that has been registered, and is able to display asset location information in 2 rooms.